Pelatihan Penggunaan Libreoffice Bagi Para Guru SD Tanah Tingal - Yuliazmi; Grace Gata; Imelda (Jurnal Pengabdian kepada Masyarakat TEKNO (JAM-TEKNO), 2021)
LibreOffice is a FOSS (Free Open Source Software) office application which is a project of The Document Foundation (TDF) organization. LibreOffice is used to create text documents, spreadsheets, presentations, and so on. LibreOffice is a solution for using an alternative use of Microsoft Office office applications with a paid license. LibreOffice uses the Mozilla Public License (MPL) version 2.0. Domestic Primary Schools in the use of ICT for teaching and learning activities have started pioneering migration using the Linux operating system and the FOSS application in 2015. Starting in the 2016/2017 academic year, it is planned to fully implement it. use of Linux for teachers, administrative staff and students. To support this, the school is doing various things to improve the competence of teachers in the use of ICT, especially the LibreOffice office application. Based on this, "Training on the Use of LibreOffice for Tanah Tingal Elementary School teachers to improve teacher competence in the use of ICT in teaching and learning activities at Tanah Tingal School" as a form of Community Service Program (PPM) which is one one tridharma from college. This training can be a useful contribution to improving the abilities of teachers in particular and students in the end.